Self-esteem and aggressive behaviour: a pilot study - Rossouw, Gabriel Johannes (Rhodes University, Faculty of Humanities, Department of Psychology, 1987)
From Introduction: "That man is an aggressive creature will hardly be disputed. With the exception of certain rodents, no other vertebrate habitually destroys members of his own species. No other animal takes positive pleasure in the excercise of cruelty upon another of his kind" (A. Storr, 1968 p. ix). It is a sombre fact that man is the cruellest and most ruthless specie that has ever walked on earth. We recoil in horror when we read the daily newspaper or in a history book of the atrocities committed by man, but as A. Storr puts it: "....., we know in our hearts that each one of us harbours within himself those savage impulses which lead to murder, to torture and to war." (p. ix). Our warranted concern with this phenomenon is portrayed by the tremendous amount of research in this field which can be sub-divided into two distinct categories. The first category consist of those that emphasize nurture in their attempt to gain a deeper understanding of human aggression, of which the behaviourists and social learning theorists are staunch supporters. Underlying their concern and endeavour is the personal belief that aggression is attributable to environmental factors. In short, they maintain that humans are not aggressive by nature and if one follows their argument to its logical conclusion it would allow for a sigh of relief and inspiration. Their research results indicate that well deliberated methods of control would most certainly result in the extinction or near extinction of aggression. The second category consist of those, notably the psycho-analytic school of thought, who emphasize nature in their understanding of human aggression and do not allow themselves the naivety of projecting aggression into environmental conditions and situations. In short, they argue that aggression is innate and serves a particular function in the psychological development of the human being. It is their contention that aggressiveness supports the individual in his drive towards independence. The aim of this paper is to present both stances and to broaden the perspective by introducing a view that straddles both nature and nurture. Following this view, of whom Rollo May (1972) is a strong supporter, to its logical conclusion would indicate that aggression is the result of nature as well as nurture and that it serves the function of re-establishing a sense of worth and significance that has otherwise been thwarted. Finally, this paper sets out to prove that aggression and violence "feeds on a low self- esteem and self-doubt" (Toch. 69, p. 212).
Keywords: Aggressiveness; Self-esteem